Transisi Kurikulum dan Dampaknya terhadap Pembelajaran di Sekolah Dasar - Juliana Margareta Sumilat; Mutia Harun (Journal on Education, 2024)
The objecive of this study is to find out the impact of curriculum transitions on learning. The research method used is the library study, which is the method of gathering data by understanding and studying theories from various literature related to research. The results of the study show that the curriculum transition that is taking place in Indonesia is to improve the quality of education. The independent curriculum aims to cover the shortcomings of the previous curricula and also or encourage students to acquire academic skills that will help them their goals and this curricule is in line with the needs of today's society. The implementation of this curriculum is expected to inspire future generations to continue to strive to improve the quality and competitiveness of their education, as well as to be a tool for achieving better results and competing in the world of national and international education.